Consumer Insights for Optimization of Industrial Systems: The Case of Consumers’ Greenwashing Perception in Adopting Single-Use Plastics Products in Padang City - Hafiz Rahman; Nurul Marliza Putri Hesti; Donard Games; Niyanta Shetye (Jurnal Optimasi Sistem Industri, 2025)
This study explicates the impact of consumer perceptions of greenwashing on the purchase intentions of single-use plastic products, specifically bottled still water and soft drinks, within the context of growing sustainability concerns. The objective is to understand how these perceptions influence consumer decisions and how the insights can inform the optimization of industrial practices related to packaging and marketing. Using a quantitative explanatory design, data was collected from no less than one hundred and sixty-eight respondents in Padang City through direct and online surveys. The sampling method is the Non-Probability Sampling method with a Purposive Sampling approach and it is directed to individuals who meet the following criteria: (1) minimum age of 17 years old; (2) domicile in Padang City; and (3) individuals or households who know bottled water and soft drinks brand. The data analysis, conducted via Structural Equation Modelling (SEM) using SmartPLS, reveals that negative perceptions of greenwashing significantly reduce purchase intentions. However, positive word-of-mouth can mitigate these effects, leading to a higher likelihood of purchase. The findings highlight the critical role of environmental awareness in shaping consumer behavior and suggest that companies should prioritize authentic sustainability practices which could be in terms of third-party certification to maintain consumer trust and optimize their product strategies. Companies are expected to be able to do business responsibly, by paying attention to the end-to-end production process that has minimal waste and minimal impact on the environment, through the development of more environmentally friendly products and optimization of waste management programs. Third-party certifications may be useful to support this effort.